(untitled) (Journal of the Digital Humanities Association of Southern Africa, 2024)
This study sets out to examine the possibility of using African languages as media of teaching and learning in South African schools. Literature is consistent that (a) language is a crucial means of communication and gaining access to important knowledge and skills, and (b) mother tongue is the only language that promotes effective teaching and learning and that any language, which is not a mother tongue, is a barrier to teaching and learning. In South Africa, there are nine African official languages, but English is the media of instruction used by South African learners, which is a barrier to teaching and learning. This study revealed that using one or two African languages may improve teaching, learning, and the academic performance of the learners, but the problem is how to implement because it will be difficult to use many African languages as media of instruction. The use of nine African languages as media of instruction in South Africa will promote tribalism, which was dominant during the apartheid era, and it will be costly to the government. Therefore, this study supports the use of English as a media of instruction because it will promote unity in South Africa, it will not be costly, and it is an international language.